Pattern of speech and language disorders in university college hospital, Ibadan (1996)
188 patients referred for speech therapy at U.C.H. Ibadan were analysed for types of speech pathology. Having ascertained the Ear, Nose and Throat conditions of the patients and with no significant medical indications, patients were promptly refered or Speech/Language assessment and therapy. The incidence of Speech/Language impairment was found to be higher in children (0-10 years) while delayed speech was found to be more prevalent. The import of public education on forms., causes, prevention and correction of speech and language defects was suggested.